2018
DOI: 10.1039/c8tc03155j
|View full text |Cite|
|
Sign up to set email alerts
|

Highly efficient, all-solution-processed, flexible white quantum dot light-emitting diodes

Abstract: Flexible information displays hold great promise for future optoelectronic applications. Herein, we report the fabrication of an efficient flexible white quantum dot (QD) light-emitting diode (QLED) with mixed red, green and blue QDs as emitters via an all-solution process. The resulting flexible QLED with a pure white emission shows high current efficiency of 10.5 cd A−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…In doing so, we first considered the possibility of mixing all sizes of emitter dots in the matrix ( Figure a), following prior art on white light emission CQD LEDs. [ 25–27 ] By mixing all three emitter QDs (λ ex = 1.3, 1.4, 1.5 µm, respectively) in the matrix QD of λ ex = 0.7 µm the resultant emission spectrum, shown in Figure 2c, failed to deliver broadband emission. The EL spectrum showed instead a strong peak around 1.5 µm.…”
Section: Figurementioning
confidence: 99%
“…In doing so, we first considered the possibility of mixing all sizes of emitter dots in the matrix ( Figure a), following prior art on white light emission CQD LEDs. [ 25–27 ] By mixing all three emitter QDs (λ ex = 1.3, 1.4, 1.5 µm, respectively) in the matrix QD of λ ex = 0.7 µm the resultant emission spectrum, shown in Figure 2c, failed to deliver broadband emission. The EL spectrum showed instead a strong peak around 1.5 µm.…”
Section: Figurementioning
confidence: 99%
“…The comparison of the device performance of green QLEDs from the previous literature studies and our study is listed in Table 2. [4][5][6]10,20,24,25,27,29,30 It is seen that our optimized device IV comprising PEDOT:PSS + BYK-P105 as the HTL and PEIE-modied ZnO as the ETL showed a very high brightness and comparable current efficiency compared with other studies. Therefore, blending BYK-P105 with PEDOT:PSS provides a successful approach to improve the performance of QLEDs.…”
Section: Resultsmentioning
confidence: 57%
“…Here, the materials of zero-dimensional (0D) CQDs and 2D CQWs are formed by IV elemental nanocrystal semiconductors (e.g., Si, Ge), the common groups being II-VI (e.g., CdSe, CdTe), III-V (e.g., InP, InAs), and IV-VI (e.g., PbSe, PbS), binary nanocrystal semiconductors, and nanocrystal semiconducting materials of ternary chalcogenide compounds AB m C n (A= Cu, Ag, Zn, Cd, etc. ; B= Al, Ga, In; C= S, Se, Te) [ 7 , 8 , 9 , 10 , 11 ]. Perovskites here refer to the materials possessing the formula ABX 3 , in which A-site is MA + , [CH(NH 2 ) 2 ] + (FA + ) or Cs + , B-site is mostly Pb 2+ , and X-site is Cl, Br, I or mixed halide systems (Cl/Br, Br/I) [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Fundamental Concepts Of Impurity-doped Nanocrystal Ledsmentioning
confidence: 99%
“…In 1994, Alivisatos et al reported the first nanocrystal LED by using CdSe colloidal quantum dots (CQDs), achieving a maximum external quantum efficiency (EQE) of 0.01% [ 6 ]. Since then, plenty of endeavors have been taken to enhance the performance (e.g., EQE, current efficiency (CE), power efficiency (PE), voltage, luminance, and stability) of CQD-LEDs [ 7 , 8 , 9 , 10 , 11 ]. Nowadays, the performance of CQD-LEDs can be comparable to or even better than that of state-of-the-art organic LEDs (OLEDs) [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%